Antifungal Activity of (+)-2,2’-Epicytoskyrin A and Its Membrane-Disruptive Action - Wulansari, Dewi; Praptiwi,; Julistiono, Heddy; Nurkanto, Arif; Agusta, Andria (Makara Journal of Science, 2016)
(+)-2,2’-Epicytoskyrin A, a bis-anthraquinone isolated from fungal endophyte Diaporthe sp. GNBP-10 associated with Uncaria gambir Roxb., was investigated for its antifungal activity. The broth microdilution method was used to determine the minimum inhibitory concentration (MIC) against 22 yeast strains and three filamentous fungi. The MICs of (+)-2,2’-epicytoskyrin A ranged from 16 to 128 µg/mL, which exhibited lower activity than the antifungal nystatin. A study of the mechanism of action revealed similar effects of (+)-2,2’-epicytoskyrin A and nystatin on Candida tropicalis at their MICs (16 and 8 µg/mL, respectively) and 2 times of the MIC. Both compounds caused cytoplasmic material and ion leakages on fungal cell, which were characterized by an increase in absorbance at 260 nm and 280 nm as well as Ca2+ and K+ ion concentrations. The morphology of the fungal cells after (+)-2,2’-epicytoskyrin A treatment was observed under a scanning electron microscope. The control cells, which were not treated with either (+)-2,2’-epicytoskyrin A or nystatin, showed a smooth surface, while the cells treated with either (+)-2,2’-epicytoskyrin A or nystatin shrank and displayed a donut-like shape. More shrinkage was observed in the 2 times MIC concentration and even more in the cells exposed to nystatin. The action of (+)-2,2’-epicytoskyrin A was proposed through membrane disruption.